Enhancing character strengths and resilience in primary education: an online Quranic stories-based program - Zekary, Samir Ahmed; Saleh, Gomaa Zakaria; Ibrahim, Ashraf Ragab; El-Hashimi, Elsayed Atef; Yussuf, Mustafa Mohamed; Nemt-allah, Mohamed Ali (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigated the effectiveness of an online Quranic stories-based program in enhancing character strengths and resilience among primary school students. Using a randomized controlled design, 64 students (aged 11-13 years) from Housh Eissa School in Egypt were assigned to experimental (n=33) and control (n=31) groups. The intervention involved ten online sessions on five major Quranic civilizations, measuring character strengths and resilience using the validated 23-item character strengths test and ego-resiliency scale. Data were collected at three time points: pre-intervention, post-intervention, and two-month follow-up. The results demonstrated significant improvements in the experimental group across all 23-character strength dimensions (p<.01, partial η² ranging from .116 to .529) and resilience (F=34.245, partial η²=.529). Notable enhancements were observed in judgment (F=11.775, partial η²=.279), self-control (F=10.269, partial η²=.252), and beauty appreciation (F=10.824, partial η²=.262). These improvements were maintained during the follow-up period, with the experimental group consistently outperforming the control group. The study suggests that online Quranic stories-based interventions can effectively enhance character strengths and resilience in primary school students, demonstrating a promising approach for character education.